Implementing Educational Projects: A Guide to Effective Management and Delivery (The Science Post, 2025)
Educational projects, ranging from curriculum reform to digital learning integration, require meticulous planning, stakeholder coordination, and adaptive leadership. This paper explores the principles of project management tailored to the educational domain. It outlines key stages of educational project implementation, highlights common challenges, and proposes best practices for successful delivery. Drawing on real-world examples and project management frameworks, this paper serves as a practical guide for educators, administrators, and policymakers engaged in projectbased initiatives within educational institutions.